2021
DOI: 10.3390/mi12091105
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Behavioral Effects of SiO2 Nanoparticle Ingestion on Daphnia magna

Abstract: The increasingly widespread use of engineered nanoparticles in medical, industrial, and food applications has raised concerns regarding their potential toxicity to humans and the environment. Silicon dioxide nanoparticles (SiO2 NPs), which have relatively low direct toxicity, have been increasingly applied in both consumer products and biomedical applications, leading to significantly higher exposure for humans and the environment. We carried out a toxicity assessment of SiO2 NPs using the common water flea D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The authors of the study demonstrated no acute toxicity of the tested silica at concentrations up to 100 mg/L. However, significant physiological and behavioral changes were observed in adults and young D. magna animals, such as changes in swimming efficiency, individual size, and reproductive impairment; these factors supported the hypothesis that SiO 2 had a negative effect on D. magna [ 40 ]. Other authors indicated that both amorphous and crystalline forms of SiO 2 could lead to lymph-node fibrosis in rats [ 41 ].…”
Section: Resultsmentioning
confidence: 67%
“…The authors of the study demonstrated no acute toxicity of the tested silica at concentrations up to 100 mg/L. However, significant physiological and behavioral changes were observed in adults and young D. magna animals, such as changes in swimming efficiency, individual size, and reproductive impairment; these factors supported the hypothesis that SiO 2 had a negative effect on D. magna [ 40 ]. Other authors indicated that both amorphous and crystalline forms of SiO 2 could lead to lymph-node fibrosis in rats [ 41 ].…”
Section: Resultsmentioning
confidence: 67%
“…After stabilisation, the swimming distance was monitored every minute for 10 min, using a millimeter paper. The latter method was modified from the protocol used by Kim et al (2021).…”
Section: Effects Of Chronic Exposure On D Magna Maturation and Reprod...mentioning
confidence: 99%
“…The heart rate was recorded as a video file for one min using an integrated PC light microscope at 4× grossing (Optika microscopes, Italy). The heart rate was manually counted using a low-speed reading (×0.3) and repeated three times, with the mean values of each sample used for comparison (Kim et al 2021).…”
Section: Heart Beat Ratementioning
confidence: 99%
“…In general, the main results have suggested that the D. magna reproduction decreased in a concentration–response pattern in all generations tested for Ag NPs, whereas TiO 2 NPs had no effect in the reproduction rate . It was also shown that SiO 2 NPs may or may not cause alterations in the reproduction rate depending on the concentration and size of NPs. Up to now, we only know the work done by Tamanaha-Vegas et al using a γ-Fe 2 O 3 nanocomposite to study the effect of the γ-Fe 2 O 3 NPs on the reproduction rate of the D. magna.…”
Section: Raman Tem Stem and Saed Analysismentioning
confidence: 99%